Intermediate-term results of trans-abdominal ultrasound (TAUS)-guided brachytherapy in cervical cancer - Ekkasit Tharavichitkul (2018)
© 2018 Objectives: To report the intermediate-term results of trans-abdominal ultrasound (TAUS)-guided brachytherapy in cervical cancer. Materials and methods: Ninety-two patients with cervical cancer (stage IB-IVA, according to FIGO staging), were treated by curative radiotherapy from February 2012 to June 2015. All patients were treated with whole pelvic radiotherapy to 50 Gy in 25 fractions and central shielding after 44 Gy, in combination with TAUS-guided brachytherapy, in order to escalate the total dose (EQD2) to the minimal dose at cervical points (in EQD2 concepts) defined by TAUS, while maintaining low doses to ICRU bladder and rectal points. The treatment results and toxicity profiles were reported. Results: At median follow-up time of 41.2 months (range 8 to 61 months) the pelvic control, disease-free survival, and overall survival rates were 84.8%, 75%, and 88%, respectively. The mean applied doses to cervix, bladder, and rectal points were 83.5, 72.3, and 76.5 Gy, respectively. Eight patients developed grade 2 Gastrointestinal toxicity. Conclusion: The 3-year results demonstrated that TAUS-guided brachytherapy is feasible and associated with excellent tumor control/toxicity rates in cervical cancer.